Nasionalisme dalam Rindu; Telaah Terhadap Puisi “Lianni Gharib” Karya Badar Syakir Sayyab: Nationalism in Longing; Study of the poem Lianni Gharib by Badar Syakir Sayyab - Syifa Ramadhanti; Ahfa Rahman Syah; Mawardi Mawardi; Lilis Malikatus Sakinah; Ika Amrikhanifah (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2025)
Nationalism is often raised in Arabic poetry, presented in various forms, to foster a spirit of change in current social dynamics. In this case, the Iraqi poem "Lianni Gharib" by Badar Syakir Sayyab also presents this through its content. This study aims to analyze nationalism in the poem "Lianni Gharib" using Roland Barthes' semiotic theory, focusing on three levels of meaning: denotative, connotative, and mythical. The method used is content analysis with a qualitative descriptive approach. The results of this study show that the poem "Lianni Gharib" represents Iraqi nationalism through the poet's emotions of longing. At the denotative level, this poem directly conveys the poet's longing for the homeland by evoking foreignness, longing, destruction, and the presence of symbols of stone, blood, and the abyss in its depiction of Iraq. At the connotative level, this longing turns into a complex emotional experience where the author suffers greatly from his unhealed longing for Iraq as well as his suffering from Iraq's very poor socio-political conditions. Meanwhile, in the mythical context, this expression of longing conveys an ideological message about the movement for change and improvement in Iraq, making it appear subtle and natural (non-political). This relates to his exile due to the political turmoil in Iraq at the time.